Pengaruh Program Keselamatan dan Kesehatan Kerja Terhadap Produktivitas Kerja pada Divisi Proyek - Sunarto Urjoyo Purba; Tatan Sukwika (The Graduate School of Sahid University, 2021)
This study aims to analyze occupational safety programs and productivity, analysis of occupational safety and health programs on the company's and analysis of the effect of occupational safety and health program variables on employee productivity. The study was conducted by analyzing questionnaires from 58 respondents of employees and contractors in the project division. The data analysis method used is statistical analysis description and path analysis. From the analysis carried out, the occupational safety and health factors that have a high influence on employee productivity are health program variables, disease prevention and measurement and monitoring with values of 18.19, 0.62, and 0.80. Implementation of safety programs to project division has been well implemented, health program variables, disease prevention and measurement and monitoring have a significant and positive effect together on productivity, pressure management and accident prevention contribute positively but not significantly to the productivity variable. With the significant influence of safety programs on work productivity, the company continues and improves the implementation of safety and requires all employees and contractors to implement safety and health following safety policies and procedures. Safety programs that have not significantly improved the concept of existing programs.